World development and economic systems : S.I. Cohen - Cohen, S. I. (Singapore World Scientific, 2015)
This book presents an integrative theory of distinct economic systems arising from different behavioral-motivational patterns associated with households, states, and firms. The author analyzes the historical evolution of these systems, evaluates their responses to systemic failures and economic performance, and projects the influence of emerging powers on system competition and global governance.
Includes bibliographical references and index.
Keywords: Quản trị kinh doanh